12-week double-blind randomized multicenter study of efficacy and safety of agomelatine (25-50 mg/day) versus escitalopram (10-20 mg/day) in out-patients with severe generalized anxiety disorder - Stein, Dan J; Khoo, Jon-Paul; Ahokas, Antti; Jarema, Marek; Van Ameringen, Michael; Vavrusova, Livia; Hӧschl, Cyril; Bauer, Michael; Bitter, Istvan; Mosolov, Sergey N; Olivier, Valérie; Matharan, Sophie; et al. (European neuropsychopharmacology, 2018)
Treatment of severely symptomatic patients with generalized anxiety disorder (GAD) raises particular concerns for clinicians. This 12-week double-blind study evaluated the efficacy of agomelatine (25-50 mg/day) in the treatment of patients with severe GAD, using escitalopram (10-20 mg) as active comparator. The primary outcome measure was the change from baseline of the total score on the Hamilton Anxiety scale (HAM-A) at week 12. Secondary outcome measures included rate of response to treatment (at least 50% score reduction from baseline) in the HAM-A psychic and somatic anxiety sub-scores, Clinical Global Impression severity and change scores, the Toronto Hospital Alertness Test, the Snaith-Hamilton Pleasure Scale, and the Leeds Sleep Evaluation Questionnaire Scores. Sixty one clinical centers (Australia, Canada, Czech Republic, Finland, Germany, Hungary, Poland, Russia, Slovakia) participated from April 2013 to February 2015. Patient characteristics and demographic data were comparable between treatment groups. Both treatments were associated with a clinically significant decrease in HAM-A total score at week 12; the non-inferiority of agomelatine versus escitalopram was not demonstrated (E(SE) = -0.91(0.69), 95%CI = [-2.26, 0.44], p = 0.195). At week 12, the response rate was 60.9% in the agomelatine group, and 64.8% in the escitalopram group. In both treatment arms, HAM-A psychic and somatic anxiety scores decreased, alertness and sleep parameters improved, and ability to experience pleasure increased. In these secondary outcome measures, there were no significant differences between the treatment groups. Agomelatine was well-tolerated, with a lower incidence of adverse events than escitalopram. Agomelatine and escitalopram are efficacious in treating GAD patients with severe symptoms.
Keywords: acetamidy; dospělí; Citalopram; Female; Anti-Anxiety Agents; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; úzkostné poruchy; Adolescent; Generalized anxiety disorder; Interview, Psychological; lidé; anxiolytika; Treatment Outcome; následné studie; Acetamides; stupeň závažnosti nemoci; citalopram; Escitalopram; Anxiety Disorders; Follow-Up Studies; Male; Aged; psychiatrické posuzovací škály; Young Adult; Agomelatine; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; interview psychologický; Middle Aged; mladiství; Psychiatric Status Rating Scales; Humans